EFEKTIFITAS BEBERAPA JENIS INSEKTISIDA TERHADAP Liriomyza sp. PADA TANAMAN BAWANG MERAH - Rinawati, Rinawati; Shahabuddin, Shahabuddin; Asrul, Asrul (AGROTEKBIS, 2018)
The purpose of this research is to know the effectiveness of insecticide type to population, Liriomyza sp attack and onion plant production. The study was conducted from February to November 2017 in Guntarano Village and at the Pest and Disease Plant Laboratory University of Tadulako Palu. This study used Randomized Block Design consisting of 4 treatments, namely control, M.anisopliae, citronella extract and insecticide Dimehipo. The results showed that the type of insecticide applied to onion crops affected the population and the attack Liriomyza sp. as well as onion plant production. Imago population Liriomyza sp. the highest was in the control treatment of 4.56 tail / trap compared to the treatment of insecticide Dimehipo 1.39 tail/trap while the treatment of gray and M.anisopliae extract of 2.22 tail / trap and 2.11 tail / trap. Attack  Liriomyza sp. highest in the control treatment was 21.2% compared with the treatment of  M.anisopliae 16.27%, the treatment of citronella 18% and the lowest in the treatment of insecticide Dimehipo 13.13%. The highest production was in the treatment of insecticides Dimehipo 6.87 tons / ha, M.anisopliae 5.11 tons / ha, citronella extrack 4.85 tons / ha and control of 3.10 tons / ha. Thus an effective insecticide suppresses the intensity of the attack, the population of Liriomyza sp. and increase the production of onion crops, namely insecticide Dimehipo.